Fucoidan-derived carbon dots against Enterococcus faecalis biofilm and infected dentinal tubules for the treatment of persistent endodontic infections - Shang Tang; Hui Zhang; Li Mei; Keke Dou; Yuying Jiang; Zhanyi Sun; Shuai Wang; Mohamed Sayed Hasanin; Jing Deng; Qihui Zhou (Journal of Nanobiotechnology, 2022)
Abstract Enterococcus faecalis (E. faecalis) biofilm-associated persistent endodontic infections (PEIs) are one of the most common tooth lesions, causing chronic periapical periodontitis, root resorption, and even tooth loss. Clinical root canal disinfectants have the risk of damaging soft tissues (e.g., mucosa and tongue) and teeth in the oral cavity, unsatisfactory to the therapy of PEIs. Nanomaterials with remarkable antibacterial properties and good biocompatibility have been developed as a promising strategy for removing pathogenic bacteria and related biofilm. Herein, carbon dots (CDs) derived from fucoidan (FD) are prepared through a one-pot hydrothermal method for the treatment of PEIs. The prepared FDCDs (7.15 nm) with sulfate groups and fluorescence property are well dispersed and stable in water. Further, it is found that in vitro FDCDs display excellent inhibiting effects on E. faecalis and its biofilm by inducing the formation of intracellular and extracellular reactive oxygen species and altering bacterial permeability. Importantly, the FDCDs penetrated the root canals and dentinal tubules, removing located E. faecalis biofilm. Moreover, the cellular assays show that the developed FDCDs have satisfactory cytocompatibility and promote macrophage recruitment. Thus, the developed FDCDs hold great potential for the management of PEIs. Graphical Abstract